Evaluating the neonatal BCG vaccination programme in Ireland. Issue 1 (December 2016) - Usher, Cara; Adams, Roisin; Schmitz, Susanne; Kieran, Jennifer; O'Flanagan, Darina; O'Donnell, Joan; Connolly, Kevin; Corcoran, Brenda; Butler, Karina; Barry, Michael; Walsh, Cathal
Abstract Background The aim of this study was to compare the cost effectiveness of the current Irish programme of universal BCG vaccination of infants versus a programme which considered selectively vaccinating high risk infants using decision analytical modelling. Methods The efficacy of the BCG vaccine was re-evaluated to inform a decision analytical model constructed to follow a birth cohort of vaccinated and unvaccinated infants over a 15 year time horizon. The number of life years gained (LYG) was the primary outcome measure and this was compared to the net cost of the vaccination strategies. Results In the base case analysis, the incremental cost effectiveness ratios (ICERs) for the universal strategy and selective strategy vs no vaccination were €204, 373/LYG and €143, 233/LYG respectively. When comparing the incremental difference in moving from the universal to the selective strategy, the selective strategy costs €1, 055, 692 less per 4.8 life years lost per birth cohort. One way sensitivity analyses highlighted that a move from the universal to the selective strategy was particularly sensitive to the estimate of vaccine efficacy against deaths, the cost of administering the vaccine and the multiplier used to apportion risk of contracting tuberculosis. Probabilistic analysis suggested that a move from a universal based strategy to a selective based strategy could be deemed cost effective (probability of cost effectiveness is 76.8 %). Conclusion The results of the study support the protective effect of the BCG vaccine in infants and quantified the cost effectiveness of the current BCG vaccination strategy and the decremental difference in moving to a selective strategy. This analysis highlights that the additional protection offered by the universal vaccination strategy is small compared to that of the selective strategy. Consideration should therefore be given to the implementation of a selective vaccination strategy, and diverting resources to improve TB case management and control.